2020
DOI: 10.3389/fphar.2020.00129
|View full text |Cite
|
Sign up to set email alerts
|

Roles and Mechanisms of Interleukin-12 Family Members in Cardiovascular Diseases: Opportunities and Challenges

Abstract: Cardiovascular diseases represent a complex group of clinical syndromes caused by a variety of interacting pathological factors. They include the most extensive disease population and rank first in all-cause mortality worldwide. Accumulating evidence demonstrates that cytokines play critical roles in the presence and development of cardiovascular diseases. Interleukin-12 family members, including IL-12, IL-23, IL-27 and IL-35, are a class of cytokines that regulate a variety of biological effects; they are clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 144 publications
(257 reference statements)
2
31
1
2
Order By: Relevance
“…In particular, the TNF‐related apoptosis‐inducing ligand (TRAIL) and the TNF‐like weak inducer of apoptosis (TWEAK) are involved in several processes related to plaque growth and instability, such as endothelial damage, basal membrane remodelling and vascular smooth muscle proliferation 117,118 . Among novel potential therapeutic target, the IL‐12 superfamily members, particularly IL‐35, have been associated with myocardial reperfusion damage in murine models 119 . Since the monoclonal inhibitor of IL‐12 ustekinumab is currently approved for the treatment of chronic inflammatory bowel diseases, 120 there is a potential rationale for clinical trials.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In particular, the TNF‐related apoptosis‐inducing ligand (TRAIL) and the TNF‐like weak inducer of apoptosis (TWEAK) are involved in several processes related to plaque growth and instability, such as endothelial damage, basal membrane remodelling and vascular smooth muscle proliferation 117,118 . Among novel potential therapeutic target, the IL‐12 superfamily members, particularly IL‐35, have been associated with myocardial reperfusion damage in murine models 119 . Since the monoclonal inhibitor of IL‐12 ustekinumab is currently approved for the treatment of chronic inflammatory bowel diseases, 120 there is a potential rationale for clinical trials.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…The in vitro study revealed that the D allele in rs28362491 polymorphism might result in reduced NF-κB1 message, thus decreasing the expression of NF-κB1 [39]. The NF-κB1 appears to be specifically involved in anti-inflammatory effects, and decreased NF-κB1 can promote the transcription of pro-inflammatory cytokines like TNF-α and IL-12 [40], which are contributors of CAD [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, when the function of IL-12 was neutralized using vaccination in LDL receptor-knockout mice, atherogenesis was reduced by 68.5% [ 130 , 131 ]. The levels of IL-12 family cytokines are also significantly higher in patients with atherosclerosis associated with cardiovascular disease [ 132 , 133 ].…”
Section: Cytokine-targeting Therapymentioning
confidence: 99%